Enhancing Structural, Thermal, and Mechanical Properties of Acacia Pennata Natural Fibers Through Benzoyl Chloride Treatment for Construction Applications - Saavedra-Flores, E (Elsevier Ltd, 2023)
In recent years, there has been growing interest in exploring natural fiber reinforced composites as potential alternatives to conventional materials in various structural applications. The aim of this study on Acacia pennata fibers (APFs) and treating them with benzoyl chloride was to explore their potential as reinforcement in construction-related materials. The aim was to investigate the physico-chemical, thermal, and mechanical properties of these fibers to understand their suitability for applications in concrete reinforcement, retrofitting, roofing, and wall panels. By enhancing the understanding of the treated fibers characteristics, this study contributes to the development of sustainable and high-performance construction materials. The fibers were extracted using both water retting and chemical retting methods. The physico-chemical properties of the fibers were assessed through X-ray diffraction (XRD) analysis, which determined a calculated crystalline index (CI) of 72.14% and a crystalline size of 2.6 nm. Thermo-gravimetric analysis was conducted to evaluate the thermal stability of the APFs, revealing a temperature of 366°C and a maximum degradation temperature of 226.7°C. Mechanical analysis included measurements of the APFs tensile strength (467.86 MPa), tensile modulus (14.62 GPa), microfibrillar angle (14.79˚), and elongation at break (3.2%). The findings derived from these analyses suggest that the APFs that underwent treatment exhibit desirable mechanical characteristics, rendering them a viable option for utilization in construction-related materials like reinforcement in concrete, retrofitting, roofing and wall Pannels. This research presents a novel exploration of Acacia pennata fibers (APFs) treated with benzoyl chloride, aiming to establish their potential as reinforcements for construction materials. While natural fiber-reinforced composites have drawn interest, the unique application of APFs in construction and their treatment with benzoyl chloride to enhance properties remain relatively unexplored in the literature. This study fills a significant gap and contributes to the advancement of sustainable and high-performance construction materials by utilizing treated APFs. The results highlight the remarkable capability of these fibers to enhance the properties of composite materials in the construction industry. © 2023 The Authors